Działania Tyberiusza w wybranych regionach jako narzędzie polityki dyplomatycznej w latach 20 p.n.e.–37 n.e. - Haba, Łukasz (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
This article is devoted to the diplomatic activities of Tiberius which can be divided into two main phases. The first period concerns the time before Tiberius became emperor (20 BCE–14 CE), whilst the second relates to his time as ruler of the Empire (14–37). The composition of the work is geographical, because in some regions Tiberius acted as a diplomatic envoy of Augustus and later as the emperor. The paper discusses his role and how effective his actions were with regards to the following regions: (I) Armenia and Parthia; (II) Pannonia; (III) Germania; (IV)Thrace; (V) Cappadocia, Commagene, Amanus and Pontus; (VI) Greek cities; (VII) Palestine and Syria.
Keywords: Tyberiusz; August; pryncypat; Imperium Romanum; Królestwo Partów; Dyplomacja w starożytności